Posthodiplostomum cuticola (Digenea: Diplostomatidae) in intermediate fish hosts: factors contributing to the parasite infection and prey selection by the definitive bird host - Ondracková, M; Simková, A; Gelnar, M; Jurajda, P (Parasitology, 2004)
Infection parameters of Posthodiplostomum cuticola, a digenean parasite with a complex life-cycle, were investigated in fish (the second intermediate host) from 6 floodplain water bodies over 2 years. A broad range of factors related to abiotic characteristics of localities, density of the first intermediate (planorbid snails) and definitive (wading birds) hosts and fish community structure were tested for their effects on P. cuticola infection in juvenile and adult fish. Characters of the littoral zone and flood duration were found to be important factors for the presence of the first intermediate and definitive hosts. Visitation time of definitive bird hosts was also related to adult fish host density. Localities with P. cuticola infected fish were visited by a higher number of bird species. Infection of P. cuticola in fish and similarities in infection among fish host assemblages were correlated with fish host density and fish species composition. Parasite infection in both adult and juvenile fishes was associated with the slope of the bank and the bottom type, in particular in juvenile fish assemblages with snail host density. We conclude that habitat characteristics, snail host density and fish community structure contribute significantly to P. cuticola infection in fish hosts.
Keywords: infekce červy třídy Trematoda; zvířata; Trematode Infections; ryby; Environment; Feeding Behavior; Life Cycle Stages; Host-Parasite Interactions; Fish Diseases; Snails; Animals; Birds; stravovací zvyklosti; Trematoda; hlemýždi; nemoci ryb; Fishes; interakce hostitele a parazita; Prevalence; stadia vývoje; ptáci; prevalence; životní prostředí